2004
DOI: 10.1111/j.1471-4159.2004.02530.x
|View full text |Cite
|
Sign up to set email alerts
|

The c‐Raf inhibitor GW5074 provides neuroprotection in vitro and in an animal model of neurodegeneration through a MEK‐ERK and Akt‐independent mechanism

Abstract: Cerebellar granule neurons undergo apoptosis when switched from a medium containing high potassium (HK) to one that has low potassium (LK). LK-induced cell death is blocked by GW5074 {5-Iodo-3-[(3,5-dibromo-4-hydroxyphenyl) methylene]-2-indolinone}, a synthetic drug that inhibits c-Raf activity in vitro. GW5074 has no direct effect on the activities of several apoptosis-associated kinases when assayed in vitro. In contrast to its effect in vitro, treatment of neurons with GW5074 causes c-Raf activation (when m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
112
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(126 citation statements)
references
References 78 publications
(88 reference statements)
14
112
0
Order By: Relevance
“…We chose the Raf-1 inhibitor GW5074 to further demonstrate the involvement of ERK in the ET receptor upregulation after SHS. The specificity and efficacy of GW5074 for inhibiting Raf-1 in-vivo has been established in previous studies [32,33]. Lakey et al and Chin et al reported that GW5074 is a potent Raf-1 inhibitor and examined the effect of GW5074 on purified Raf-1 and confirmed that GW5074 selectively inhibits Raf-1 in vivo .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We chose the Raf-1 inhibitor GW5074 to further demonstrate the involvement of ERK in the ET receptor upregulation after SHS. The specificity and efficacy of GW5074 for inhibiting Raf-1 in-vivo has been established in previous studies [32,33]. Lakey et al and Chin et al reported that GW5074 is a potent Raf-1 inhibitor and examined the effect of GW5074 on purified Raf-1 and confirmed that GW5074 selectively inhibits Raf-1 in vivo .…”
Section: Discussionmentioning
confidence: 83%
“…Raf phosphorylates MEK1/2, which in turn phosphorylates and activates ERK1/2 and then leads to activation of transcription factors [32]. The ERK1/2 pathway is a major effector of Raf.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both U0126 and SB386023 decreased organ culture-induced ET B receptor upregulation (Henriksson et al, 2004). Raf-1 (c-Raf) is 20 a MAPK required for Ras/MEK/ERK signal transduction, which is the first enzyme in the MAPK cascade consisting of the three protein kinases Raf-1, MEK and ERK (Chin et al, 2004). Inhibition of Raf-1 attenuated cigarette smoke-induced expression of endothelin receptors in mice (Lei et al, 2008).…”
Section: The Role Of Mapk In Vascular Endothelin Receptor Upregulationmentioning
confidence: 99%
“…Control animals received vehicle injections. Doses were chosen according to our preliminary studies and literature [8,9].…”
Section: Drugsmentioning
confidence: 99%